Academic Dishonesty in Prospective Religion Teachers - Herdian Herdian; Dyah Astorini Wulandari (Psikologia : Jurnal Psikologi, 2017)
The purpose of this study is how the forms of dishonest behavior in situations doing paper work, mid semester exam and final exam of the semester and describe the purpose of behaving dishonestly. Participants in this study are 29 students of 4th semester of Islamic studies education program at university x in Purwokerto. This research uses qualitative method with vignette open questionnaire data retrieval tool known as method to reveal values in individual and data analysis using content analysis. Based on the results of this study revealed that the task situation is the most used situation by students to do academic dishonesty. Academic forms of academic dishonesty work on paper assignments, mid semester exam and final semester exam is asking / asking answers, cheating / looking at friends' answers, quoting blogs, copying paste, copying answers, opening small papers. While the purpose of academic disagreement on the situation of doing paper assignments, mid semester exam and final exam of the semester that is to be / easy to do, work completed / quickly completed, for friends to teach / get answers, not difficult in doing, accurate answers, good value, -same cackling with friends and borrowing to copy.